Caesarean scar ectopic pregnancy: a rare case report - Swamy, Mamatha; R. N., Thejashwini; T., Nisarga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Caesarean scar ectopic is one of the rarest among all ectopic pregnancies. It is defined as a blastocyst implantation on a previous caesarean scar. The incidence of caesarean scar ectopic has increased due to rise in number of caesarean deliveries. Early diagnosis by using ultrasonography and prompt management improves the outcome by allowing preservation of future fertility. It is very important because any delay can lead to increased maternal morbidity and mortality. We are reporting a rare case of gravida3 para1 live1 abortion1 with previous one caesarean delivery, diagnosed as caesarean scar ectopic pregnancy with the help of ultrasonography. Patient underwent uterine artery embolization (UAE) after failed medical management followed by hysteroscopy and ultrasound guided dilatation and evacuation, and on histopathology examination caesarean scar pregnancy was confirmed.